2022
DOI: 10.3390/bs12100361
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sensory Cues on Immersive Experiences for Fostering Technology-Assisted Sustainable Behavior: A Systematic Review

Abstract: Games are consistently acknowledged as a powerful approach that can significantly impact people’s behavior towards living in a sustainable way. Sensory cues are regarded as influential factors in facilitating immersive experiences in gamified applications to foster sustainable behavior. As our perception of an environment is influenced not only by what we can see but also by additional sensory input such as sound and touch, additional sensory information can be part of the participant’s experience. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 111 publications
(141 reference statements)
1
3
0
Order By: Relevance
“…Thus, the use of environments such as VR and AR seems to be an upcoming answer to these issues since it creates rich sensory and emotional experiences [33][34][35]. Studies have found that the optimal way to promote sustainable behavior change and awareness is to trigger students' emotions [75]. Therefore, the results of our study manifest previous findings by Dubé et al [14] and their prediction of VR as an emerging technology in education.…”
Section: State Of the Art Of Digital Tools For Fostering Environmenta...supporting
confidence: 82%
“…Thus, the use of environments such as VR and AR seems to be an upcoming answer to these issues since it creates rich sensory and emotional experiences [33][34][35]. Studies have found that the optimal way to promote sustainable behavior change and awareness is to trigger students' emotions [75]. Therefore, the results of our study manifest previous findings by Dubé et al [14] and their prediction of VR as an emerging technology in education.…”
Section: State Of the Art Of Digital Tools For Fostering Environmenta...supporting
confidence: 82%
“…Incorporate Rhythmic Songs: Utilize songs with appropriate rhythms to assist users in controlling the compression rhythm during CPR. Music as an auditory sensory cue can enhance the level of immersion in the learning process ( 65 ). Additionally, studies have confirmed its positive impact on first aid training interventions ( 51 , 52 ).…”
Section: Methodsmentioning
confidence: 99%
“…The influence of VR on affective states extends to various domains, including tourism, education, language learning, and historical education [26][27][28]. Additionally, it was found that using VR in history education can promote enjoyment and influence morality, further emphasizing its impact on affective states [29]. For instance, the Palace Museum (Beijing, China) has created an interactive experience program based on VR technology, featuring the famous painting "Along the River During the Qingming Festival".…”
Section: Impact Of Vr On Affective Statesmentioning
confidence: 99%